Comparative Analysis of AES and RSA with Other Encryption Techniques for Secure Communication - Prashant; MD Sohail Haque; Amrinder Kaur; Pankaj Yadav (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In today’s digitized era, where the whole world is interconnected and every information about individuals are collected, it is important to process and store the data such that it is safe from unauthorized access. Encryption is used to turn the plain text into cipher text which makes the data unreadable, thus maintaining its confidentiality and integrity. Among the several encryption methods available, Advanced Encryption Standard (AES) and Rivest Shamir Adleman (RSA) are popularly used due to their effectiveness and efficiency. However, alternative encryption techniques exist, each offers different level of security and performance. This study presents a thorough comparative analysis of AES and RSA alongside other encryption methods to assess their suitability for secure communication. Factors such as encryption strength, computational complexity, key management, scalability, and versatility are examined to provide a comprehensive understanding of each technique’s strengths and weaknesses. By scrutinizing these aspects, this research aims to offer insights for decision-makers in selecting the most suitable encryption method tailored to specific requirements and constraints.